KAJIAN STRATEGI PEMBELAJARAN MATEMATIKA BERBASIS ONLINE (Study Of Online Mathematics Learning Strategy) - Hamdan Sugilar; Tika Karlina Rachmawati; Asep Suratman; Rahayu Kariadinata (Jurnal Ilmiah Didaktika, 2021)
The purpose of this study was to determine the online-based learning strategy in the form of variables to consider in online learning, the role of parents in online learning, government policies in online learning during the new normal period, and evaluation of online learning in the form of student attitudes towards online learning in the new normal period. The research method is literature study and survey by distributing questionnaires. The population of students at two Senior High Schools in Bandung Regency, the sample of students who filled out the google form amounted to 740 students at two Senior High Schools in Bandung Regency. The research instrument was in the form of a questionnaire distributed via the google form application. The results show that several important points are needed in online-based learning as follows: it is necessary to pay attention to variables in online learning, the role of parents, government policies, and the results of the evaluation of online mathematics learning from students.